Trolling as a Collective Form of Harassment: An Inductive Study of How Online Users Understand Trolling. (June 2020) - Ortiz, Stephanie M.
Rising media and academic concerns for the social implications of online trolling require that scholars understand how everyday users conceptualize trolling. The validity of survey instruments may potentially be at risk if online users and academics, who subsequently advocate for interventions, have competing understandings of trolling. Surveying 120 US-based online users, I find that the spectrum of behaviors classified in the literature as "trolling" do not resonate with respondents. Instead, respondents report that harassment on the basis of race and gender is indicative of trolling. These results suggest a disconnect between academic definitions of trolling that focus on prosocial or humor-based forms of trolling and lay definitions which foreground identity-based harassment and harm. Current instruments that assess trolling behaviors and experiences do not attend to this definition of trolling as identity-based harassment, calling into question construct validity. Furthermore, sociologists identify identity-based harassment as a form of discrimination in other domains of social life, but present measures of discrimination do not consider the online domain. This suggests that studies of everyday discrimination and the implications of mistreatment should extend to online spaces, where racism and sexism are reproduced.